Wahyu Alkitabiah dalam Tinjauan Hermeneutika Ricoeur - Leo Kleden (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article attempts to explain the idea of revelation in the Scripture according to Paul Ricoeur's hermeneutic philosophy. This paper consists of two parts. The first part describes the theory of text in Ricoeur's hermeneutics. Ricoeur's most important contributions to this section are his description of threefold semantic autonomy: semantic autonomy with respect to the author's subjective intention outside the text, semantic autonomy with respect to the original cultural context in which the text was written, and semantic autonomy with respect to the original audience or addressee. An important consequence of semantic autonomy is that interpretation of a text is never reproductive but productive. The second part explains that the language of Scripture is much more like poetic language than scientific language. Poetic language is the language of disclosure, which expresses a deeper dimension of reality. The next five literary genres in the Scriptures are discussed, through which divine revelation is expressed: namely, narrative, prophetic, prescriptive, wisdom and hymnic genre. With that Ricoeur shows the richness of biblical revelation in its various dimensions, which together form “a polysemic and polyphonic concept of revelation”.Keywords: text, discourse, literary genre, semantic autonomy, revelation, narrative, hymn